Selective emulsion liquid membrane extraction of silver from photographic waste industries - Mat, Hanapi (Faculty of Chemical and Natural Resources Engineering, 2006)

(untitled)
The field of liquid membrane technology is currently undergoing a rapid expansion in research as well as its application as an industrial separation process. Liquid membrane can be manipulated to selectively separate a specific solute from a mixture and even to extract a solute against its concentration gradient. A liquid membrane system comprises of three liquid phases; feed phase, liquid membrane organic phase and receiving phase. Liquid membrane can be prepared using support or as emulsion (unsupported) liquid membrane. Emulsion liquid membrane is a liquid membrane in which the membrane phase of an emulsion is dispersed into the feed phase to be treated. This method was investigated as an alternative process for the recovery of silver from photographic waste, which contains various metals ions such as silver, iron, sodium and potassium. The important parameters governing the extraction process of silver such as agitation speed, homogenizer speed, surfactant and carrier concentrations, type of diluents, treat ratio and types of stripping solution were investigated. This process has been conducted in a batch system using a mixer-settler. The results show that the mobile carrier Cyanex 302 is selective towards silver and almost completely extract silver over the other metals that existed in the photographic waste. The optimum silver extraction was obtained by using 0.03 M Cyanex 302, 3 % (w/v) Span 80, 250 rpm stirring speed, 1.0 M thiourea in 1.0 M H2SO4 stripping agent, 1:5 of treat ratio, and kerosene as a diluents. The experimental result also shows that the emulsion liquid membrane system could be recycled twice having 80% of silver was extracted. In addition, theoretical studies show that the developed model could predict the extraction performance of the system understudied as obtained from experimental data.